Level of Shooting Ability in Football Games at the Long Gathering Club, Padang Guci Hilir, Kaur Regency - Megi Personi; Deffri Anggara (Sinar Sport Journal, 2023)
This study aims to determine the ability to shoot in a soccer game at Padang Guci Hilir Long Gathering, Kaur Kaur District. This type of research is a qualitative descriptive research. The research sample is 25 people. The instrument used in this study was the Football shooting test. Where the results of the level of shooting ability in soccer games at the Padang Guci Hilir Gathering in Padang Guci Hilir Regency in this study show the classification of "good" to "very poor". Then where are the results of the final shooting ability test in the soccer game at the Padang Guci Hilir Long Gathering, Kaur Kaur Regency, as follows: that of the 25 players at the Padang Guci Hilir Gathering, Kaur Regency. As many as 3 people (12%) have very less category. As many as 5 people (20%) have less category. As many as 12 people (48%) have sufficient category. As many as 4 people (16%) have a good category and as many as 1 person (4%) have a very good category. Then it can be concluded that the Football Game Shooting Ability Test at the Padang Guci Hilir Club Arisan Panjang, Kaur Kaur Regency, is in the Enough category, namely 12 athletes or with a percentage of (48%).